The Effect of Workbook on Illness Cognition in Coronary Heart Disease Patients - Aan Nur'aeni; Ristina Mirwanti; Anastasia Anna (Padjadjaran Acute Care Nursing Journal, 2019)
Introduction: Recurrence of coronary heart disease (CHD) occurs due to non-compliance patients in managing CHD. One predictor of compliance with CHD management is illness cognition (IC), and IC can be improved through illness stimuli that can be done through health education in this study through workbooks. Purpose: This study aimed to identify the effect of the workbook on illness cognition in CHD patients. Methods. This research was a quasi-experimental with pretest-posttest control design. A pretest was done to the patient who was treated in the Cardiac Intensive Unit; posttest was carried out at the end of the first and second month after the pretest. The population was all post-acute CHD patients who were admitted to the cardiac intensive unit in one of the referral hospital in West Java, Indonesia. Purposive sampling was used and obtained 39 respondents who were divided into control and intervention groups. The instrument used was the illness cognition questionnaire (ICQ). Data were analyzed using the mean, median, percentage, and to estimate the effect of the workbook to the patients' IC used Wilcoxon and Friedman test. Results: The results showed an increase in acceptance and perceived benefits for both groups while in the helplessness showed the decrease scores. The p-value of IC comparison in the pre-test, post-test I, and II between groups for helplessness, acceptance, and perceived benefits were 0.118; 0.376; and 0.424, respectively. Besides, the p-value for differences of IC within control and intervention groups was less than 0.05. Conclusions: The workbook in this study generally did not provide significant IC changes to respondents.